Role of vitamin D receptor gene polymorphisms in aplastic anemia: a case–control study from China. (28th March 2016) - Yu, W.; Ge, M.; Shi, J.; Li, X.; Zhang, J.; Wang, M.; Shao, Y.; Zheng, Y.
Summary: Introduction: Vitamin D receptor (VDR) gene and its polymorphisms are highlighted as candidate components for susceptibility to various autoimmune diseases. The aim of this study was to investigate the role of VDR polymorphisms (rs2228570, rs1544410, rs7975232, and rs731236) in aplastic anemia (AA). Methods: In this case–control study, the genotyping of VDR rs1544410 (c.1024 + 283G>A), rs7975232 (c.1025‐49G>T), and rs731236 (c.1056T>C) polymorphisms was conducted using polymerase chain reaction (PCR)–ligase detection reaction, while the genotyping of rs2228570 (c.2T>C) was detected by PCR–restriction fragment length polymorphism. Results: The frequencies of GG genotype and G allele of rs1544410 were significantly higher in patients with AA than in controls. Further analysis indicated that rs1544410 and rs7975232 polymorphisms were correlated with the risk to nonsevere AA, while rs2228570 was relevant to severe AA. Moreover, TT carriers of rs2228570 were closely associated with a poor response to treatment and a higher risk of myelodysplastic syndrome/acute leukemia transformation, while CT carriers more easily evolved to overt paroxysmal nocturnal hemoglobinuria. Conclusions: VDR polymorphisms may contribute to susceptibility to AA and influence the severity and prognosis of AA in a Chinese population.